Farm food safety plans: customizing educational materials for small-scale and campus-based farms - Morris, Rachael E., author; Bunning, Marisa, advisor; Uchanski, Mark, committee member; Stone, Martha, committee member; Sullins, Martha, committee member (Colorado State University. Libraries, 2017)
A comprehensive farm food safety plan is an integral part of all growing operations, regardless of size, output, or production practice. As small-scale and campus-based, student-run farms grow in popularity, there is an increasing need to establish the concept of comprehensive produce safety practices as a vital part of the farming process. Moreover, the passing of the Food Safety Modernization Act (FSMA) in 2011 addresses mandated accountability for large-scale agriculture within the Produce Safety Rule, but leaves many small farms exempt from regulation, including the types of farms targeted within this study. A need for a curriculum addressing produce safety on campus farms and small-scale operations, and lack of literature surrounding food safety training curriculum development drove the research design for this project. The components of this study were three fold: 1) university and college campus farm managers (n=12) from 14 states were surveyed on current practices; 2) classroom and on-farm presentations were developed and delivered to Colorado State University horticulture students (n=54), and a pre-and post- questionnaire was delivered to assess learning objectives; and 3) three on-line modules and a 27-page farm plan template were developed for Colorado growers, detailed during a webinar for Colorado Fruit and Vegetable Growers Association (CFVGA) members (participants n=33). Results offered positive a relationship between resource delivery and food safety knowledge for both students and growers. The pre-and post-questionnaire responses showed change (p≤0.05), including Likert scale questions stating that farm workers (p=0.001) and volunteers (p<0.0005) should receive food safety training. Post-webinar polling questions revealed that 100% (n=21) of voluntary respondents learned something new during the webinar, which focused on utilization of resources to build and modify farm food safety plans for any growing operation. With the national movement toward a prevention-focused food safety strategy, the need for implementing better produce safety practices has been identified as a top priority. Review and feedback from this study will aid in the continued development of materials for both campus and small-scale growers to expand their food safety practices.